Evaluation of a Great Agrovoltaic Implementation in an Isle Using SWOT and TOWS Matrices: Case Study of Gran Canaria Island (Spain) - Antonio Pulido-Alonso; José C. Quintana-Suárez; Enrique Rosales-Asensio; José J. Feo-García; Néstor R. Florido-Suárez (Land)
Nowadays, we are heading towards global decarbonisation, with each sector involved contributing partial solutions to the problem, without realising that an overall vision is necessary. Photovoltaics emerged as a technology that requires a lot of surface area, which is why it has been integrated into buildings and other human infrastructures (BPVI). The effects of the implementation of AVS on an island have been analysed, observing the territory’s energy use, population, and social and topographical realities, collecting all the peculiarities that could be affected by a massive implementation of this technology. The method to be followed is a SWOT and TOWS analysis, widely employed in all types of scientific studies. The increase in the island’s resilience has been assessed, as has its decreasing its dependence on the outside. In this case, it has been observed that conventional PV is currently being installed on agricultural land to decarbonise electricity production, which mostly relies on oil and does not consider that the island is a territory with a high food dependence on the outside; a high unemployment rate; a high factor of soil desertification, meaning fires are frequent; a high rate of abandonment of agricultural land; and a shortage of flat land. Therefore, we affirm that the island’s carbon footprint will increase by not taking all these factors into account. In addition to punishing the local economy by destroying fertile soil, local food and jobs, the current method of energy production increases the need for subsidies to import food products from abroad. In addition, we claim that the use of AVS reduces the water needs of the crop, which is relevant on an island with great water scarcity. It is concluded that 11 of the 17 UN Sustainable Development Goals would be improved with the use of agrovoltaic technology.